Sustainable waste management proceedings of the international symposium held at the University of Dundee, Scotland, UK on 9-11 September 2003 - Dhir, Ravindra K.; Newlands, Moray D.; Dyer, Thomas D. (Thomas Telford, 2003)
This volume presents part of the proceedings of two symposia held under the umbrella of Advances in Waste Management, an international meeting organised by the University of Dundee's Concrete Technology Unit.